2016
DOI: 10.3390/cancers8100091
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Tumor-Specific Immunity Using PDT

Abstract: Photodynamic therapy (PDT) is a cancer treatment with a long-standing history. It employs the application of nontoxic components, namely a light-sensitive photosensitizer and visible light, to generate reactive oxygen species (ROS). These ROS lead to tumor cell destruction, which is accompanied by the induction of an acute inflammatory response. This inflammatory process sends a danger signal to the innate immune system, which results in activation of specific cell types and release of additional inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 78 publications
1
68
1
1
Order By: Relevance
“…Several landmark reviews by Castano et al (2006), Mroz et al (2011) and Meading et al . (2016) have described in depth how PDT is capable of eliciting tumor‐specific adaptive immunity . In this review, we will focus only on the major steps involved in achieving an adaptive antitumor response following photodynamic insult to tumors to bridge the fundamentals of photochemistry, ICD and adaptive immunity with the potential for enriching the T‐cell repertoire (Fig.…”
Section: Activation Of the Adaptive Immune Systemmentioning
confidence: 99%
“…Several landmark reviews by Castano et al (2006), Mroz et al (2011) and Meading et al . (2016) have described in depth how PDT is capable of eliciting tumor‐specific adaptive immunity . In this review, we will focus only on the major steps involved in achieving an adaptive antitumor response following photodynamic insult to tumors to bridge the fundamentals of photochemistry, ICD and adaptive immunity with the potential for enriching the T‐cell repertoire (Fig.…”
Section: Activation Of the Adaptive Immune Systemmentioning
confidence: 99%
“…Ample evidence shows that both the innate and adaptive immune systems participate in PDT-induced tumour elimination (Nowis et al 2005;Castano et al, 2006). The immune response is activated by PDT-induced tumour cell death or damage, which triggers the release of various damage-associated molecular patterns (DAMPs) including heat shock protein 70 (HSP70), calreticulin (CRT), high-mobility group box 1 (HMDB1), and ATP (Korbelik 2006;Maeding et al 2016;Tanaka et al 2016). A particularly immunogenic type of cell death is necrosis, where a lot of DAMPs are released, but apoptotic and stressed cells contribute as well, especially if the extent of damage is large and/or rapidly peaks upon PDT application (Korbelik 2006).…”
Section: Pdt and The Immune System Pdt-mediated Immune Responses In Cmentioning
confidence: 99%
“…103,104 Therefore, oxygen self-enriched nanoparticles are beneficial for not only the enhanced PDT effect but also for overcoming chemoresistance. 106 Kabingu et al demonstrated that local PDT can inhibit the growth of the primary tumor and the untreated distant tumors due to the infiltration of CD8 + T cells. Tumor cells undergoing apoptosis or necrosis release tumor-associated antigens.…”
Section: Recent Advance Of Nanoparticle-based Pdtmentioning
confidence: 99%